Impact of short videos on digital journalism in social media - Brigas, Joaquim; Gonçalves, Fátima; Marques, Henrique; Gonçalves, Jorge (Revista de Ciencias Sociales, 2023)
As social media continues to evolve, visual information has become a significant aspect in the media sector. Short videos on Instagram have revolutionized digital journalism and impacted management processes and journalistic practices in many ways. This paper aims to examine how reels are reshaping the way the news organizations make visual information available to the audience. Through a quantitative and qualitative approach, the profile of four of the main Portuguese national newspapers on the social network Instagram is analyzed. In the period under analysis, all of them increased the number of followers, presented differences and similarities in the use of strategies in the distribution of reels, used short videos in their strategies in order to be able to involve their target audience more. Furthermore, they discussed how the use of reels on Instagram has transformed communication management, such as the adoption of multimedia reporting and the integration of social media in news distribution. This article provides valuable insight into the evolving nature of digital journalism and the impact of social media on management processes and journalistic practices.